Sexual offences: a comparative textual foundations - Mohamad Yunus, Mohamad Ismail (Penerbit UTHM, 2019)
Every human society attempts to control sexual behaviour since sex represents a rich source of conflicts that can disrupt orderly social processes. Human sexuality is too powerful and explosive a force for any society to allow its members to complete sexual freedom. Some limits must be imposed, some rules agreed upon and some enforcement mechanisms devised to implement the observance of the rules. Throughout the ages, communities have used various combinations of law, religion and morality to achieve control. Not surprisingly, the regulation of sexuality has been a central feature of virtually every known legal system. This book focuses on the area of divine law relating to sexual crimes. Chapter I begins with a brief history of law relating to sexual crimes, then chapter 2 speaks about the religious perspectives on sexual crimes. Chapter 3 gives an introduction to Islamic law, which is called “Shariah” in Arabic. The definition of Shariah, its sources and the types of punishment and its exceptions are briefly explained so that it may help the readers to understand the whole idea of this book more clearly and lastly, chapters 4 and 5 explain on sexual crimes under the Islamic penology, such as, introduces and elaborates various types of sexual crimes in Islamic law such as the law of zina (illicit sexual intercourse), the law of rape, the law of marital rape, the law of sodomy, the law of bestiality and their punishments.